2014
DOI: 10.1002/jee.20063
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Cognitive Career Theory to Assess Student Outcomes of Group Design Projects in Statics

Abstract: Background Engineering programs strive to retain students and prepare them for engineering careers. Introducing group design projects into courses may help keep students interested while also improving their learning outcomes. Purpose/Hypothesis This study measures differences in student content knowledge and intention to persist in engineering between an intervention section with group design projects and a comparison section without. We hypothesized that students in the intervention section would show an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 36 publications
1
28
0
2
Order By: Relevance
“…The development of these components of professional responsibility may be the key to how competitions or service learning may extend project-and problem-based curricular learning. Project-based learning supported the development of understanding project goals and the relationship to project outcomes (Atadero, Rambo-Hernandez, & Balgopal, 2015). Engineering competitions may provide a more intense experience than classroom projects that contributed to the more sophisticated nuances discussed by students in this study.…”
Section: Discussionmentioning
confidence: 81%
“…The development of these components of professional responsibility may be the key to how competitions or service learning may extend project-and problem-based curricular learning. Project-based learning supported the development of understanding project goals and the relationship to project outcomes (Atadero, Rambo-Hernandez, & Balgopal, 2015). Engineering competitions may provide a more intense experience than classroom projects that contributed to the more sophisticated nuances discussed by students in this study.…”
Section: Discussionmentioning
confidence: 81%
“…SCCT has been used to explore students' interest in pursuing an engineering major (e.g., Lent et al 2005), engineering student retention (e.g., Atadero, Rambo-Hernandez, & Balgopal, 2015), engineering alumni's career choices (e.g., Brunhaver, 2015), and the retention of women engineers in the workforce (Fouad & Singh, 2011;Singh et al, 2013). In the EMS, SCCT was used to develop and explore the relationships between the measures of innovation attitudes, interests, and goals which in turn, has informed our current investigation of career certainty and indecision (Gilmartin et al 2017).…”
Section: Design Of the Survey Instrument And Datasetmentioning
confidence: 99%
“…Lent and colleagues have shown that SCCT can successfully describe this choice process in many types of post secondary students, engineering students in particular [15][16][17][18] .…”
Section: Making a Career Choice: Social Cognitive Career Theory As A mentioning
confidence: 99%